Effect of biofilm structural deformation on hydraulic resistance during ultrafiltration: A numerical and experimental study. (15th November 2018) - Jafari, Morez; Desmond, Peter; van Loosdrecht, Mark C.M.; Derlon, Nicolas; Morgenroth, Eberhard; Picioreanu, Cristian
Abstract: Biofilm formation in membrane systems negatively impacts the filtration system performances. This study evaluated how biofilm compression driven by permeate flow increases the hydraulic resistance and leads to reduction in permeate flux. We analysed the effect of biofilm compression on hydraulic resistance and permeate flux through computational models supported by experimental data. Biofilms with homogeneous surface structure were subjected to step-wise changes in flux and transmembrane pressure during compression and relaxation tests. Biofilm thickness under applied forces was measured non-invasively in-situ using optical coherence tomography (OCT). A numerical model of poroelasticity, which couples water flow through the biofilm with biofilm mechanics, was developed to correlate the structural deformation with biofilm hydraulics (permeability and resistance). The computational model enabled extracting mechanical and hydrological parameters corresponding to the experimental data. Homogeneous biofilms under elevated compression forces experienced a significant reduction in thickness while only a slight increase in resistance was observed. This shows that hydraulic resistance of homogeneous biofilms was affected more by permeability decrease due to pore closure than by a decrease in thickness. Both viscoelastic and elastoplastic models could describe well the permanent biofilm deformation. However, for biofilms under study, a simpler elastic model could also be used due to the small irreversible deformations. The elastic moduli fitting the measured data were in agreement with other reported values for biofilm under compression. Biofilm stiffening under larger flow-driven compression forces was observed and described numerically by correlating inversely the elastic modulus with biofilm porosity. The importance of this newly developed method lies in estimation of accurate biofilm mechanical parameters to be used in numerical models for both membrane filtration system and biofouling cleaning strategies. Such model can ultimately be used to identify optimal operating conditions for membrane system subjected to biofouling. Highlights: OCT was coupled with a poroelastic Fluid-Structure Interaction biofilm model. Mechanical properties of biofilms were determined in-situ by a non-destructive approach. Homogeneous biofilm structure deforms reversible in compression/relaxation cycles. Biofilm hydraulic resistance was governed by permeability change due to pore closure. Biofilm stiffening at large fluxes can be explained by a reduction in porosity.